Safety and efficacy of esketamine for postoperative analgesia in pediatric patients with hypospadias - Xu, Yong; Chen, Quan; Li, Ping; Song, Xingrong (Frontiers in Surgery, 2023)
Objective To explore the safety and efficacy of the combination of continuous intravenous infusion of esketamine with sacral block for postoperative analgesia in pediatric patients undergoing surgery for hypospadias Methods Pediatric patients (n = 77) undergoing surgery for hypospadias were randomized into two groups: a hydromorphone group (H group, initial dose, 0.02 mg/kg; maintenance dose, 0.01 mg/kg/h) or an esketamine group (E group, initial dose, 0.3 mg/kg; maintenance dose 0.15 mg/kg/h). Caudal epidural block involved injection of 0.2% ropivacaine 1 ml/kg through the sacral hiatus. Age, weight, grade of hypospadias, intraoperative blood loss, operative time, and awaking time of patients were recorded. The Face, Legs, Activity, Cry and Consolability (FLACC) scale and Ramsay sedation scores were recorded when leaving the PACU (0 h) and at postoperative 2, 6, 12, 24, 36, and 48 h. The Pediatric Anesthesia Emergence Delirium Scale (PAED), incidence of hypotension, respiratory depression, nausea and vomiting and pruritus, and the time to first bowel movement after surgery were recorded. Results There were no significant differences in demographic and clinical characteristics between the H group and the E group. There were no significant differences in FLACC scores at postoperative 0, 2, 6, 12, 24, 36, and 48 h in intra-group and inter-group comparisons. There were no significant differences in Ramsay sedation scores at postoperative 0, 2, 6, 12, 24, 36, and 48 h in the intra-group comparisons. Ramsay sedation scores were significantly lower at postoperative 2, 12, and 36 h in the H group compared to the E group. There were no significant differences in the PAED scale or incidence of nausea and vomiting or pruritus between the H group and the E group. The incidence of hypotension and respiratory depression was significantly lower, and the time to first bowel movement was significantly shorter in the E group compared to the H group. Urinary tryptophan, 5-hydroxytryptamine and substance P levels were significantly lower but arginine was significantly higher in the E group compared to the H group. Conclusions The combination of continuous intravenous infusion of esketamine with sacral block provided safe and effective postoperative analgesia for pediatric patients undergoing surgery for hypospadias. Trial registration Chinese Clinical Trial Register ChiCTR2200066967. Clinical trial registry URL: http://www.chictr.org.cn/edit.aspx?pid=185042&htm=4